A Critical Review on the Book Theoretical Foundations from the Collection of Art in Islamic Civilization - Mehran Houshiar (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Explaining the basics and knowing the alphabet of each phenomenon is necessary to understand the concepts, content foundations, and existential philosophy. This is especially important in the field of humanities and has been considered by contemporary thinkers. Due to its geographical extent and semantic values, Islamic art has certain theoretical and practical principles that are very similar to the basis of traditional arts. The compiler of the book "Theoretical Foundations" has tried to explain the principles, principles and concepts of this art by combining the knowledge and opinion of experts and researchers active in various fields of Islamic art into a credible and valid scientific text. In this article, while introducing the published sections and articles, describing and interpreting the main themes mentioned in each text, it has been criticized and evaluated. The findings of this critical study indicate that the unity of existence and the existence of common and hidden beliefs in all works show a semantic continuity and dependence on a single origin. The publication of the book "Theoretical Foundations" in order to introduce the characteristics and moral, value and mystical views of Islamic art is a useful step that has been made available to researchers, students and enthusiasts in this field today as a valid and reliable source.